The lived experiences of Black women who completed their doctorate through a cohort model Community College Leadership Program in the United States - King, Millette (My University, 2025)
This hermeneutic phenomenological study was designed to understand the lived experiences of Black women who completed their doctorate through a cohort model Community College Leadership Program. Black women were not completing doctoral degrees at the same rate as their peers. The National Center for Education Statistics (2023) states that in 2020-21, 61% of the doctorates earned by females were White females, 12% were earned by Black females, 10% earned by Hispanic females, 13% earned by Asian/Pacific Islanders and .4% American Indian/Alaska Native (NCES, 2023). The following research questions guided this study: What are the lived experiences of Black women who have completed their doctorate through a cohort model Community College Leadership Program? What factors supported Black women’s completion of the Community College Leadership Program? This study utilized the hermeneutic circle to gain insight into the lived experiences of 14 Black woman who completed a cohort model community college leadership program. Themes that emerged from the semi structured interviews, when viewed through the conceptual lens of Black Feminist Thought, included that Black women formed strong bonds with their cohort members that lasted well beyond the doctoral journey. The participants in this study were impacted by COVID during their journey both in a positive and negative way. Family illness and divorce also impacted the doctoral journey of the women interviewed. Finally, relationships with faculty, staff and peers impacted the doctoral journey of Black women in this study. Recommendations for future research include exploring the lived experiences of other marginalized populations, conducting a qualitative study to survey all people of color that attend a community college leadership program, exploring other doctoral concentration areas and research on how cliques impact the learning environment in cohort models.
Keywords: Lived experiences; Black women; Community college leadership program; Doctoral program; Phenomenology; Cohort model